Compatible or incompatible?: Intelligence and human rights in terrorist trials - Quirine Eijkman (Amsterdam Law Forum, 2012)
This article focuses on the special criminal procedures for the use of intelligence in terrorism-related court cases in Canada, France, the Netherlands and the United Kingdom. Since 9/11 and the terror attacks in London and Madrid, both gathering intelligence as well as the prosecution of suspects of terrorist crimes have become strategic tools in countering terrorism. By reviewing the special procedures for the use of intelligence in terrorist trials, their compatibility with human rights standards, including the right to fair trial, is discussed. Among others concerns include: the extent to which disclosure is made possible and to who. The differences in criminal procedures for the use of intelligence in terrorist trials raise questions when intelligence information origins from a third state, in which different regulations with regard to disclosure of information apply.